Effects if in-service computer training course on teachers' computer literacy, attitudes toward computers, frequency of use and confidence in integrating computers in the teaching-learning process - Yong, Chee Kieng (2009)
This research explored the effects of in-service computer training courses on teachers’ computer literacy, attitudes toward computers, frequency of and confidence in integrating computer in PPSMTI. In addition, this study also looked at how demographic variables such as age, gender and prior computer experiences impacted on the four dependent variables, and the relationships among them. The findings also showed that there were significant relationships between computer literacy, attitudes toward computers, frequency of and confidence in integrating computer.